(untitled) (Perner’s Contacts, 2015)
An article is focused on a benefit of urban traction units with tilting system particularly in regional transport, to reduce travel times and increase the competitiveness of railway transport. The paper describes the importance of their utilization in such traffic especially if the state of infrastructure is unable to provide options of higher efficiency for railway undertakings and the investments for line optimization are not available, so undertakings cannot be more efficient in use of classical vehicles of conventional design. However, this does not mean that the state of the infrastructure cannot offer the possibility of using tilting system.